Mapping Alzheimer’s disease pathology using free water through integrated analysis of plasma biomarkers, microstructural DTI metrics, and macrostructural MRI measures - Bo-Hyun Kim; Daeun Shin; Sung Hoon Kang; Hyemin Jang; Jihwan Yun; YuHyun Park; Henrik Zetterberg; Kaj Blennow; Fernando Gonzalez-Ortiz; Nicholas J. Ashton; Sung Tae Kim; Hee Jin Kim; et al. (Scientific Reports)
Abstract Alzheimer’s disease (AD) is characterized by amyloid-beta (Aβ) and tau pathologies that drive neuroinflammation and neurodegeneration. Free water (FW), a diffusion tensor imaging (DTI) metric reflecting extracellular fluid changes, has emerged as a sensitive marker of neuroinflammation. This study examined the role of FW in AD and its associations with plasma biomarkers, brain structural measures, and cognitive decline. We analyzed 968 participants across the AD continuum from Samsung Medical Center. Plasma biomarkers were measured using Single Molecule Array technology. DTI metrics (FW, fractional anisotropy (FA), and mean diffusivity (MD)) and structural MRI-derived hippocampal volume and cortical thickness were assessed. Plasma phosphorylated tau 217 (pTau217) significantly correlated with FW in both white matter (WM) and gray matter (GM), but not with FA or MD. All DTI metrics were associated with reduced hippocampal volume and lower cortical thickness. Mediation analyses revealed that FW in WM and GM had both direct and indirect associations with cognitive decline, while FA and MD were indirectly linked to cognitive outcomes through structural measures. These findings support FW as a sensitive marker of neuroinflammation, linking microstructural changes to macrostructural changes and cognitive outcomes. Integrating plasma biomarkers, DTI, and MRI may improve understanding of AD pathophysiology and support the development of targeted diagnostic and therapeutic approaches.